2007
DOI: 10.1152/ajpheart.00626.2006
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of both α1A- and α1B-adrenergic receptor subtype signaling is required to inhibit neointimal formation in the mouse femoral artery

Abstract: A. Blockade of both ␣ 1A-and ␣1B-adrenergic receptor subtype signaling is required to inhibit neointimal formation in the mouse femoral artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In addition, all α 1 -AR blockades may be required for enhanced vascular contractility. A similar phenomenon has been observed in our previous study (Hosoda et al 2007). Single deletion of α 1A -AR or α 1B -AR subtype genes does not inhibit the neointimal formation after vascular injury in the femoral artery, while deletion of both the α 1A -AR and α 1B -AR subtype genes significantly inhibits it (Hosoda et al 2007).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, all α 1 -AR blockades may be required for enhanced vascular contractility. A similar phenomenon has been observed in our previous study (Hosoda et al 2007). Single deletion of α 1A -AR or α 1B -AR subtype genes does not inhibit the neointimal formation after vascular injury in the femoral artery, while deletion of both the α 1A -AR and α 1B -AR subtype genes significantly inhibits it (Hosoda et al 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Single deletion of α 1A -AR or α 1B -AR subtype genes does not inhibit the neointimal formation after vascular injury in the femoral artery, while deletion of both the α 1A -AR and α 1B -AR subtype genes significantly inhibits it (Hosoda et al 2007). These past and present observations suggest that each α 1 -AR can cooperate and compensate the receptor function when the other receptor is absent (Hosoda et al 2007;Sanbe et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were placed into restraint tubes over a warming plate, to keep the body temperature at around 37 1C during the measurement, and the blood pressure tail cuff was attached. After a period of acclimation, a total of 30 cycles per animal was decided on to optimize the number of measurements, according to literature (Johns et al, 1996;Hosoda et al, 2007). The first 10 cycles were not used in the final analysis.…”
Section: Hemodynamic Evaluationmentioning
confidence: 99%
“…In rat aorta, both α 1A -and a 1B -adrenoceptors are involved in trophic effects [149], and in mouse femoral arteries, employing gene knockout technology, it has been demonstrated that both α 1A -and α 1B -adrenoceptors are required for neo-intimal formation (no single knockout was effective) [68].…”
Section: Vascular Responses Mediated By α 1b -Adrenoceptorsmentioning
confidence: 99%